Lensless in-line digital holography for dynamic applications - Singh, Vijay Raj (2008)
Digital holography (DH), as a tool of optical metrology, is able to address the challenges of recent requirements from technological developments. The aim of the present work is to develop digital dynamic holography as a metrological tool for both transmission and reflection applications. A lensless in-line digital holographic microscopy system is proposed and its performance for dynamic 3D imaging and micro-measurements is presented in this thesis.